Kick it like Ballack: The effects of goalkeeping gestures on goal-side selection in experienced soccer players and soccer novices - Weigelt, M.; Memmert, D.; Schack, T. (Journal of Cognitive Psychology, 2012)
The present experiment on soccer penalty kicking investigates the influence of goalkeeping gestures on goal-side selection in experienced soccer players and novices. Facing a penalty situation, participants viewed a goalkeeper and a soccer goal. In the action selection task, they kicked to the wider side of the goal, whereas in the perception task, they gave a verbal response to indicate the position of the goalkeeper. To this end, the goalkeeper was displaced at different distances to the left or right of the goal centre and depicted either in a regular goalkeeping posture, or with a pointing gesture to the left or right. Results showed that the goalkeeper's position on the goal line systematically affected goal-side selection in both experienced players and novices. Participants kicked to the wider goal side more often in the action selection task, even when they were not aware of the displacement in the perception task. Performance was further influenced by the goalkeeping gesture, with more kicks directed opposite to the pointing direction. These effects were stronger for novices. It is concluded that the simultaneous processing of implicit and explicit stimulus information influences goal-side selection in soccer penalty shooting.